Contextualizing Marshall McLuhan - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2023)
My thesis is that the Canadian Renaissance specialist and media ecology theorist and Catholic convert Marshall McLuhan (1911-1980; Ph.D. in English, Cambridge University, 1943) is an analogist. McLuhan himself developed the thesis that the Victorian Jesuit poet and Catholic convert Gerard Manley Hopkins (1844-1889) is an analogist in his 1944 article “The Analogical Mirrors,” using Hopkins’ poem “The Windover” to discuss the analogical mirrors. Because I claim that McLuhan is an analogist, I explore that broader context of analogical thought in Western cultural history. In addition, I suggest that McLuhan himself might also be characterized as a practical mystic which is how he himself characterizes G. K. Chesterton (1874-1936) in his 1934 article “G. K. Chesterton: A Practical Mystic.”